Crystal Plasticity Finite Element Simulation Study on Thread Rolling Pure Aluminum. Issue 4 (March 2021) - Hu, Zhiqing; Zhang, Yuheng; Guo, Liming
Abstract: In order to study the effects of grain orientation on thread rolling deformation, the mechanical performance was analyzed from a microscopic perspective. The Voronoi method was employed to establish a polycrystalline model and a user-defined material subroutine (UMAT) was adopted. Meanwhile the crystal plasticity finite element method (CPFEM) was used to simulate the deformation behavior of the grain on thread rolling process. The simulation results show that the deformation degree of the grain is different due to the different initial grain orientation and the representative element strain curve is more accurate after homogenization. It is also indicated that the initially activated slip systems cause the movement of the other slip systems. By analyzing the rotation of the grain orientation and the evolution of the texture through the pole figure, it can be seen the CPFEM results show high consistency with the test results of the electron back scatter diffraction (EBSD).